ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP BRAND AWARENESS KOPI TUKU - Ramadanty, Nur Evitriana; Rimenda, Tetty; Abrianto, Heri (Politeknik Negeri Ambon, 2025)
Introduction: The purpose of this study is to investigate the impact of Electronic Word of Mouth (E-WOM) on Kopi Tuku's brand awareness as a result of its naming rights agreement with MRT Cipete Raya.Methods: This quantitative study used a causal design and survey methodologies, with 150 respondents who either rode the Jakarta MRT between February and May 2025 or were aware of the sponsorship due to social media exposure. A systematic questionnaire was used to collect data, which was then analysed using SPSS 30's multiple linear regression.Results: The findings of this study indicate that Electronic Word of Mouth (E-WOM) plays a crucial role in promoting Kopi Tuku brand awareness, particularly through the naming partnership of the Cipete Raya MRT station. Respondents who were familiar with Kopi Tuku through social media or had used the MRT reported that the information they obtained from others' digital media experiences had a significant impact on their view of the brand. In other words, the more favourable discussions or evaluations about Kopi Tuku that circulate online, the stronger the brand's identification and recall among consumers. This conclusion underscores the significance of a successful E-WOM strategy in expanding a brand's reach, particularly in public venues such as mass transit. Keywords: brand awareness, E-WOM, Kopi Tuku, MRT Jakarta, naming rights.